Deformation and fracture of circular tunnels under non-tectonic stresses and its support control. Issue 5 (31st March 2022) - Du, Shaohua; Li, Diyuan; Ruan, Bo; Wu, Genshui; Pan, Bao; Ma, Jinyin
Abstract: The excavation stability of tunnel is a key problem in tunneling engineering. A mechanical model is developed to determine the boundary curve of the plastic zone and the principal stress distribution of the surrounding rock of a circular tunnel under non-tectonic stress. Specifically, the effects of different influence factors on the shape of the plastic zone and the principal stress of the surrounding rock are quantitatively analyzed. Subsequently, the Mohr-Coulomb failure criterion is utilized to determine the yield failure of the surrounding rock mass. Furthermore, technical approaches and control measures for supporting the surrounding rock are put forward. In particular, the "long and short" coordinated hierarchical support technology with "anchor cables (or long bolts) + bolts" as the main support strategy has been recommended. Finally, the proposed support technology is validated for several typical tunnels by the numerical simulation method. The results indicate that the stability of the surrounding rock of a circular tunnel can be improved by restraining the malignant extension of the plastic zone, improving the principal stress environment, and allowing uniform distribution of the plastic zone within the controllable range of the support system. These results are helpful for optimization of support technology to stabilize the surrounding rock of a circular tunnel under non-tectonic stresses.